Influence of molecular width on the thermal expansion in solids. (1st November 2019) - Rather, Sumair A.; Saraswatula, Viswanadha G.; Sharada, Durgam; Saha, Binoy K.
Abstract : It has been shown that the thermal expansion would be higher in a direction along which the molecular width is shorter and it would be smaller if the molecular width is longer along that direction. Abstract : A thermal expansion study has been performed on seven systems. Four of the systems contain π–π stacking interaction and two linear molecules form chains in their crystal structures, whereas the last one is a two-dimensional coordination polymer. It has been shown that smaller molecular width along a particular direction leads to larger thermal expansion coefficient along that direction because intermolecular junctions are closely spaced in that direction.